Gammadelta receptor bearing T cells in scleroderma: enhanced interaction with vascular endothelial cells in vitro - Kahaleh, M B; Fan, P S; Otsuka, T (Clinical immunology (Orlando, Fla.), 1999)
In view of the documented perivascular mononuclear cell infiltration in the involved organs in scleroderma (SSc) and the reported accumulation of gammadelta-T cells in SSc skin and lung, we evaluated gammadelta-T cell interaction with endothelial cells (EC) in vitro. gammadelta- and alphabeta-T cells were isolated from BPMN of SSc patients with early diffuse disease and of matched control subjects by an immunomagnetic method after stimulation with mycobacterium lysate and interleukin-2 for 2 weeks. Lymphocyte adhesion, proliferation, and cytotoxicity to EC were investigated. SSc gammadelta-T cells adhered to cultured EC and proliferated at higher rates than control cells. Furthermore, significant EC cytotoxicity by SSc gammadelta was seen. The cytotoxicity was blocked by addition of anti-gammadelta-TCR antibody and by anti-granzyme A antibody but not by anti-MHC class I and II antibodies. Expression of granzyme A mRNA was seen in five/five SSc gammadelta-T cells and in one/five control cells. alphabeta-T cells from both SSc and control subjects were significantly less interactive with EC than gammadelta-T cells. The data demonstrate EC recognition by SSc gammadelta-T cells and propose gammadelta-T cells as a possible effector cell type in the immune pathogenesis of SSc.